2021
DOI: 10.1186/s12888-021-03308-w
|View full text |Cite
|
Sign up to set email alerts
|

The psychotropic effect of vitamin D supplementation on schizophrenia symptoms

Abstract: Background Schizophrenia is a multifactorial disease involving interactions between genetic and environmental factors. Vitamin D has recently been linked to many metabolic diseases and schizophrenia. Vitamin D plays essential roles in the brain in the context of neuroplasticity, neurotransmitter biosynthesis, neuroprotection, and neurotransmission. Vitamin D receptors are demonstrated in most brain regions that are related to schizophrenia. However, very few studies in the literature examine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 46 publications
(67 reference statements)
0
4
0
Order By: Relevance
“…Clinical assessment scales such as the Assessment of Negative Symptoms (SANS) and the Assessment of Positive Symptoms (SAPS) have shown positive effects when Vitamin D is added to the treatment. These results provide promising possibilities for treatment [45].…”
Section: Vitamin D Supplementation and Schizophreniamentioning
confidence: 68%
“…Clinical assessment scales such as the Assessment of Negative Symptoms (SANS) and the Assessment of Positive Symptoms (SAPS) have shown positive effects when Vitamin D is added to the treatment. These results provide promising possibilities for treatment [45].…”
Section: Vitamin D Supplementation and Schizophreniamentioning
confidence: 68%
“…Furthermore, there was a positive correlation between the level of vitamin D and the volume of the medial orbitofrontal cortex, as well as a negative correlation with the ICVF value of PPOC, MCP, and forceps major. Previous studies have also found that vitamin D supplementation can improve total attention span and positive and negative symptoms in schizophrenia [53] . Therefore, individuals at high risk of schizophrenia and depression should be encouraged to obtain sunlight exposure to maintain optimal vitamin D levels.…”
Section: Discussionmentioning
confidence: 86%
“…Neriman et al. reported the same results in schizophrenic patients after 8 weeks of vitamin D supplementation with dosage of 50 000 IU per week 27 . Vitamin D supplementation in vitamin D deficient individuals improves mental health but such beneficial effects in healthy adults are not provided by literature.…”
Section: Discussionmentioning
confidence: 90%
“…reported the same results in schizophrenic patients after 8 weeks of vitamin D supplementation with dosage of 50 000 IU per week. 27 Vitamin D supplementation in vitamin D deficient individuals improves mental health but such beneficial effects in healthy adults are not provided by literature. It has been shown that the co‐administration of vitamin D and probiotic had higher health benefits, such as mental health, than its comparators did.…”
Section: Discussionmentioning
confidence: 99%